1995
DOI: 10.1021/ac00114a003
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenic Properties of Untreated and Poly(ethylene oxide)-Modified Polymeric Matrixes Useful for Preparing Intraarterial Ion-Selective Electrodes

Abstract: In vitro platelet adhesion studies are used to compare the thrombogenic properties of various polymer matrices useful for preparing implantable ion-selective membrane electrodes. Conventional plasticized poly(vinyl chloride) and alternate polyurethane materials (Tecoflex, Pellethane) doped with proton- (tridodecylamine) and potassium-selective (valinomycin) ionophores are shown to be potentially thrombogenic. Incorporation of high molecular weight block copolymers of poly(ethylene oxide) and poly(propylene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 31 publications
1
95
0
Order By: Relevance
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serious disadvantages are (a) natural polymers are frequently immunogenic, (b) these polymers typically decompose or undergo pyrolytic modification at temperatures below their melting point, thereby precluding the convenience of high-temperature thermoplastic processing methods (such as melt extrusion) during the manufacturing of the implant, and (c) since they are derived from animal or plant sources, natural variability in (63,64). These include poly(hydroxyl ethyl methacrylate) (59), PEG (60), and PVA (65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Hydrogels are three-dimensional polymeric networks, which adsorb and retain large amounts of water and are highly permeable to small molecules.…”
Section: Biocompatible Materials Coatingsmentioning
confidence: 99%
“…Although the pH response of the polymer membrane using SR is good, it shows a non-linear response over a working range [14,17]. Other membrane materials, such as polyurethane and polyethylene oxide, were cross-linked by exposing the matrices to UV light [18,19]. The above reports exhibited a good response for pH only in the range of 2 -10, while the response was not good over pH 10.…”
Section: Introductionmentioning
confidence: 99%